Quantifying preference for social stimuli in young children using two tasks on a mobile platform - Dubey, Indu; Brett, Simon; Ruta, Liliana; Bishain, Rahul; Chandran, Sharat; Bhavnani, Supriya; Belmonte, Matthew K.; Estrin, Georgia Lockwood; Johnson, Mark; Gliga, Teodora; Chakrabarti, Bhismadev; on behalf of the START consortium (PLOS ONE, 2022)
Children typically prefer to attend to social stimuli (e.g. faces, smiles) over non-social stimuli (e.g. natural scene, household objects). This preference for social stimuli is believed to be an essential building block for later social skills and healthy social development. Preference for social stimuli are typically measured using either passive viewing or instrumental choice paradigms, but not both. Since these paradigms likely tap into different mechanisms, the current study addresses this gap by administering both of these paradigms on an overlapping sample. In this study, we use a preferential looking task and an instrumental choice task to measure preference for social stimuli in 3–9 year old typically developing children. Children spent longer looking at social stimuli in the preferential looking task but did not show a similar preference for social rewards on the instrumental choice task. Task performance in these two paradigms were not correlated. Social skills were found to be positively related to the preference for social rewards on the choice task. This study points to putatively different mechanisms underlying the preference for social stimuli, and highlights the importance of choice of paradigms in measuring this construct.